An investigation of the psychological, physiological and endocrinological factors underlying two types of alcoholism - Loebenstein, Larry (Not Specified, 2024)
Fifteen delta and eleven gamma alcoholics were given a moderate dose of alcohoL Changes in extroversion, neuroticism, anxiety, assertiveness, Basal Skin Conductance and urinary levels of epinephrine and norepinephrine were measured. The changes that significantly differentiated the gamma group from the delta group were those measured by the psychological variables. In the sober state, measures of extroversion, anxiety and assertiveness, also differentiated the two groups. Although the physiological and biochemical changes were significant within each group, their differential responses were not significant. The results have therapeutic implications.